2008
DOI: 10.1097/olq.0b013e31815ed7b2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Testing-Only “Express” Visit Option to Enhance Efficiency in a Busy STI Clinic

Abstract: The triage system at DMHC effectively selects clients at highest risk for STI and increases clinic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 7 publications
1
40
2
Order By: Relevance
“…In the Denver study, it had declined to 46 min and 52 min in the ETS from 105 min and 85 min in comprehensive routine visits among female and male clients respectively. 14,15 Our study showed no substantial difference in testing for or detection of chlamydia before and after ETS for low-risk clients. However, in Denver Metro Health Clinic, the detection of chlamydia was 2.4 times higher among males and 1.7 times higher among females when comparing comprehensive to express visits; the Sydney study did not examine testing or diagnosis rates of these STIs in their study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the Denver study, it had declined to 46 min and 52 min in the ETS from 105 min and 85 min in comprehensive routine visits among female and male clients respectively. 14,15 Our study showed no substantial difference in testing for or detection of chlamydia before and after ETS for low-risk clients. However, in Denver Metro Health Clinic, the detection of chlamydia was 2.4 times higher among males and 1.7 times higher among females when comparing comprehensive to express visits; the Sydney study did not examine testing or diagnosis rates of these STIs in their study.…”
Section: Discussionmentioning
confidence: 88%
“…However, in Denver Metro Health Clinic, the detection of chlamydia was 2.4 times higher among males and 1.7 times higher among females when comparing comprehensive to express visits; the Sydney study did not examine testing or diagnosis rates of these STIs in their study. 14,15 The prevalence of chlamydia is~4.6% in heterosexuals under 29 years old in Australia. 16 If ETS had not been introduced, some of these individuals may not have been seen, due to clinic capacity, and this would constitute a missed opportunity to screen.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we implemented "express" testing, which is an alternate testing protocol that (1) uses non-invasive testing, (2) relies on less intrusive sexual health historytaking, and (3) reduces HIV pre-test risk reduction counselling (Knight et al, 2013;Rukh et al, 2014;Shamos et al, 2009). To assist others who may wish to replicate our approach, herein, we detail our model of express testing, which is unique from those previously created.…”
Section: Introductionmentioning
confidence: 95%
“…More persons now seek testing, but without corresponding increases in service time or human resources in STI clinics (Heijman et al, 2007;Knight et al, 2013;Rukh et al, 2014;Shamos et al, 2009). Consequently, some individuals who attend these clinics are unable to obtain testing due to either long wait-times or capacity issues -with capacity issues occurring when the number of patients who present for care exceeds the number that can be seen based on the healthcare professional staffing number or compliment on a given day (Heijman et al, 2007;Knight et al, 2013;Rukh et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation